THE EFFECT OF “PERMATA-KU” EXERCISES ON THE IMPROVEMENT OF COMPUTER VISION SYNDROME SCORE - Made Ayu Kusuma Dewi; Fifin Luthfia Rahmi; Arnila Novitasari Saubig; Hari Peni Julianti (Jurnal Kedokteran Diponegoro)
Background : Most human activities cannot be separated from the use of computers. Long-term and uncontrolled use of computers can lead to Computer Vision Syndrome (CVS). According to the Ministry of Health of the Republic of Indonesia (KEMENKES) CVS can be handled with ergonomics use of computers resultantly reducing the impact of computer exposure. Education on ergonomics use of computer and PERMATA-KU exercise is expected to improve CVS scores.